IMPLEMENTASI PERATURAN DAERAH PROVINSI NOMOR 3TAHUN 2015 TENTANG BANTUAN HUKUM BAGI MASYARAKAT MISKIN - Citra Buana; Mexsasai Indra; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Legal aid is a special legal service provided to the poor who require free defense, both outside and inside the court, criminal, civil and administrative, from someone who understands the ins and outs of legal defense, principles and rules law, and human rights.In the Criminal Procedure Code (KHUAP). Legal assistance only regulates the conditions for obtaining legal assistance, does not clearly explain what is meant by legal aid itself as contained in Article 56 paragraph (2) which reads: "a legal adviser appointed to act as referred to in paragraph (1) , provide free legal assistance ".This type of research can be classified in the type of sociological juridical research, because in this study the authors directly conduct research on the location or place studied to provide a complete and clear picture of the problem under study. This research was conducted at Pekanbaru Legal Aid Institute - Indonesian Legal Aid Foundation, and Legal Bureau of Riau Province Secretariat, while population and sample are all parties related to the problem studied in this research, data source used primary data, secondary data, and tertiary data, data collection techniques in this study were conducted with questionnaires, interviews, and literature review.From the results of research problems there are three main things that can be concluded. First, the Implementation of Provincial Regulation No. 3 of 2015 on Legal Assistance for the Poor Being able to be done well, so that the implementation does not work. Secondly, the obstacles faced in the Implementation of this Regulation are the absence of governor's rules or regulations, not yet the implementation of the local regulation of the Minister of Home Affairs, and the unfinished discussion of the budget for legal aid programs for the poor in riau province. Third, the efforts undertaken by the Government in overcoming obstacles from the implementation of the legal aid program that is a social assistance fund (Bansoso). Suggestion Writer, First, in implementing legal aid program that is supposed to make preventive effort like socialization, workshop, and others. Second, by the provincial government, it is necessary to fix internal and external factors. Thirdly, the Riau Province Pemritah is more active in learning or introducing legal aid programs to the poor who are both in court and outside court.Keywords: Implementation, Local Regulation, Legal Aid, Poor People